CHARACTERISTICS OF KNOWLEDGE, ATTITUDE AND BEHAVIOR ABOUT HIV/AIDS IN INDONESIA 2017 - Aprilla, Gabe Gusmi (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: According to the 2017 IDHS, in 2016 an estimated 620.000 thousand people were living with HIV AIDS (PLWHA), around 48.000 people with new HIV sufferers and about 38.000 deaths related to HIV/AIDS. Methods: This study used a review study and descriptive statistical analysis to know the description of the characteristics of Indonesian knowledge, attitudes and behavior about HIV/AIDS. The data source in this study is secondary data from the Demographic and Health Survey 2017. The data used are secondary data that has been analyzed univariately in the form of a percentage then reviewed with some research literature and then summarized into a series of information describing the characteristics of knowledge, attitudes and behavior about AIDS. Result: Percentage of married women and men who had heard about HIV/AIDS, respectively 82.4% (49.627 respondents) and 82.9% (10.009 respondents). As many as 79% of women refuse to have sexual relations with their husbands if they know that their husbands have had sex with other women and 75.1% ask their husbands to use condoms when having sex if they know that their husbands have an STI. As many as 85.1% of women and 85.7% of men have a discriminatory attitude towards people with HIV/AIDS. The behavior of married men who had paid for sexual intercourse 3.7%, who paid for sexual intercourse in the last 12 months was 0.9%. Based on the level of education and wealth of both women and men, the higher the level of education and wealth, the better the knowledge, attitudes and behavior will be. Based on sources of information about HIV/AIDS, both women and men get the most information from television. Recommendation: It is recommended that health workers be able to provide more education on HIV/AIDS with various methods of approach.